The Effect of Personal Selling and Consumer Behavior on Purchasing Decisions Yakult in Mojokerto - Ino Angga Putra; Henny Zuli Astuti; Khotim Fadhli (INCOME: Innovation of Economics and Management, 2021)
The purpose of the study is a) to find out the influence of Yakult Lady's personal sales on Yakult's purchase decisions in Mojokerto and b) to find out the influence of consumer behavior on Yakult's purchasing decisions through Yakult Lady in Mojokerto. The type of research used is quantitative research. The research sample is a community of Yakult customers in mojokerto area with sampling technique is purposive sample. While the subject of the study was the customers of Yakult beverages a total of 16 respondents. Data collection is done in 2 ways, namely interviews and the dissemination of questionnaire questionnaires. The results of the questionnaire were conducted data analysis using validity test, reliability test, and linear regression analysis test through calculation with SPSS application. The Influence of Yakult Lady's Personal Sales and Consumer Behavior on Purchasing Decisions where variable Personal Selling sig value 0.516 > 0.05 and t value count 0.668 < 2.160 (t table). This indicates that the Personal Selling variable has no influence on Purchase Decision and variable Consumer Behavior sig value of 0.000 < 0.05 and t value count 4,871 > 2,160 (t table) so as to show that variable Consumer Behavior there is an influence on Purchase Decision.